Investigation of natural gas theft by magnetic remanence mapping. - Dobó, Zsolt; Kovács, Helga; Tóth, Pál; Palotás, Árpád B. (Forensic Science International, 2014)
Natural gas theft causes major losses in the energy industry in Hungary. Among the non-technical losses occurring in natural gas networks, fraudulent residential consumption is one of the main factors. Up to 2014, gas meters that are most widely used in residential monitoring are manufactured with ferromagnetic moving components, which makes it possible to alter or disrupt the operation of the meters non-intrusively by placing permanent magnets on the casing of the meters. Magnetic remanence mapping was used to investigate a sample of 80 recalled residential meters and detect potentially fraudulent activity. 10% of the meters were found suspect by magnetic remanence measurement, of which 50% were confirmed to be potentially hijacked by further mechanical investigation. The details of the technique are described in this paper, along with experimental results and the discussion of the analysis of the real-world samples.